The 1st English Letters Undergraduate Conference 8th August 2017 - - (English Letters Department Sanata Dharma University Yogyakarta Indonesia, 2017)
This book containing 45 topics/articles, presented by around 60 students of 12 universities. The participants, all the members of the program commitee and Universitas Sanata Dharma which gives full support to the conference